Personality Traits and Career Role Enactment: Career Role Preferences as a Mediator - de Jong, Nicole; Wisse, Barbara; Heesink, José A. M.; van der Zee, Karen I. (Frontiers in Psychology, 2019)
It has been argued that how a person’s career unfolds is increasingly affected by his or her own values, personality characteristics, goals and preferences. The current study addresses the issue of how we can explain that personality traits are associated with the enactment of certain career roles. Two survey studies (e.g., a 2 wave worker sample and a cross-sectional worker sample) were conducted to investigate the relationships between personality traits, career role preferences and career role enactment. As expected, results indicate that peoples’ personality traits predicted the preference for certain roles in the work context which, in turn, predicted the career roles they actually occupy. Specifically, our findings show that Extraversion, Conscientiousness and Openness to experience influence various career role preferences (i.e., Maker, Expert, Presenter, Guide, Director and Inspirer role preferences) and, subsequently, the enactment of these career roles. Other traits, such as Neuroticism and Agreeableness, seem less important in predicting role preferences and subsequent role enactment. These results underline the importance of acknowledging not only individual trait differences but especially role preferences in explaining how careers develop over time. Further implications, limitations and research ideas are discussed.